2020
DOI: 10.1101/2020.11.08.373522
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The DEAD-box RNA helicase Ded1 from yeast is associated with the signal recognition particle (SRP), and its enzymatic activity is regulated by SRP21

Abstract: The DEAD-box RNA helicase Ded1 is an essential yeast protein involved in translation initiation. It belongs to the DDX3 subfamily of proteins implicated in developmental and cell-cycle regulation. In vitro, the purified Ded1 protein is an ATP-dependent RNA binding protein and an RNA-dependent ATPase, but it lacks RNA substrate specificity and enzymatic regulation. Here we demonstrate by yeast genetics, in situ localization and in vitro biochemical approaches that Ded1 is associated with, and regulated by, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 102 publications
1
0
0
Order By: Relevance
“…The more than four-fold increase in crosslinks under the glucose-depletion conditions was consistent with Ded1 interacting with ribosome-associated complexes during translation as we expected an increased expression of vacuolar proteins under these conditions. Consistent with this result, we found that Ded1 has high binding affinity for SCR1 RNA in vitro, and the RNA-dependent ATPase activity of Ded1 is inhibited by SRP21 [82].…”
Section: Ded1 Crosslinks Mostly To Mrnassupporting
confidence: 85%
“…The more than four-fold increase in crosslinks under the glucose-depletion conditions was consistent with Ded1 interacting with ribosome-associated complexes during translation as we expected an increased expression of vacuolar proteins under these conditions. Consistent with this result, we found that Ded1 has high binding affinity for SCR1 RNA in vitro, and the RNA-dependent ATPase activity of Ded1 is inhibited by SRP21 [82].…”
Section: Ded1 Crosslinks Mostly To Mrnassupporting
confidence: 85%